Perbandingan Tingkat Kebugaran Jasmani Siswa Ekstrakurikuler Futsal di SMAN 1 Sumenep dan SMAN 2 Sumenep - Irwin Rismawan; Nur Ahmad Arief (Journal on Education, 2024)
Physical fitness is the condition of the body carrying out an activity without experiencing fatigue, so that it can carry out various daily activities. For everyday life, fitness is very important especially for high school students who take part in futsal extracurriculars. So students are required to maintain their body fitness by doing lots of active movement or exercising. By maintaining fitness, high school students can carry out activities with enthusiasm without feeling excessively tired.The research aims to measure the extracurricular fitness component of students at SMAN 1 Sumenep and SMAN 2 Sumenep, namely the cardiovascular endurance fitness component using the MFT (Multistage Fitness Test) test by running back and forth over a distance of 20 meters. This research uses a quantitative approach and is non-experimental research. This research also uses a comparative design to compare different samples.Based on the results of fitness level test at SMAN 1 Sumenep and SMAN 2 Sumenep. The data for futsal extracurricular students at SMAN 1 Sumenep has an average score of 43.3867, while the result for futsal extracurricular students at SMAN 2 Sumenep have an average score of 42.5600. The results of the two schools only differ by 0.8267. Which means there is no significant difference. So futsal extracurricular students at SMAN 1 Sumenep and SMAN 2 Sumenep have relatively the same level of physical fitness.